1981
DOI: 10.1017/s0033291700041210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in the response to neuroleptics in schizophrenia: a psychopharmacogenetic study

Abstract: SynopsisA psychopharmacogenetic strategy was used to investigate a genetic heterogeneity model of schizophrenia. This model consisted of various genetic subtypes represented by patients classified hypothetically according to the types and genealogical (Mendelian) patterns of illnesses in first-degree relatives. The effect of neuroleptics on these subtypes (drug x genetic subtype interactions) were tested for evidence of post-treatment responses which discriminated between them. The findings revealed that schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…On the one hand, some neuroleptics, e.g. thioridazine, may have antidepressive effects (32); on the other, neuroleptics have been accused of causing depression (33). There is no doubt that the issue of pharmacogenic neuroleptic-induced depression currently remains controversial (34).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some neuroleptics, e.g. thioridazine, may have antidepressive effects (32); on the other, neuroleptics have been accused of causing depression (33). There is no doubt that the issue of pharmacogenic neuroleptic-induced depression currently remains controversial (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dopamine blockade by a neuroleptic drug could theoretically lead to anhedonia and, perhaps, depression. Indeed, a state of dysphoria is commonly described by neuroleptic-treated patients (34), a number of older anecdotal reports have suggested a link between neuroleptic use and depression (35)(36)(37)(38)(39), and one study found more anhedonia and depression in maintenance-phase schizophrenic patients who were taking neuroleptics than in others who were not (33). Another study found a positive relationship between haloperidol plasma levels and depressive symptoms in the context of a positive association between extrapyramidal symptoms and depressive symptoms (40), and impairments of quality of life related to neuroleptic-induced dysphoria have been reported (41).…”
Section: Neuroleptic-induced Dysphoriamentioning
confidence: 99%
“…Although DSS are described in neuroleptic-naive schizophrenic patients having a first episode, 9 patients receiving conventional antipsychotic drugs may have higher rates. 39,40 Several lines of evidence suggest that neurolepticinduced dysphoria may not encompass full criteria for a depressive disorder, 41 but nonetheless may adversely affect functional well-being. 42,43 In our investigation, the absence of a placebo arm prevented the determination of the disease-associated base rate of treatmentemergent DSS.…”
Section: Commentmentioning
confidence: 99%